1996
DOI: 10.1021/ja961682m
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Catalyst Controlled Diastereoselection and Regioselection in Intramolecular Carbon−Hydrogen Insertion Reactions of Diazoacetates

Abstract: Individual enantiomers of substituted cyclohexyl diazoacetates or 2-octyl diazoacetates matched with a configurationally suitable chiral dirhodium(II) carboxamidate catalyst provide an effective methodology for the synthesis of lactones with exceptional diastereo- and regiocontrol. Enantiomerically pure (1S,2R)-cis-2-methylcyclohexyl diazoacetate forms the all-cis-(1R,5R,9R)-9-methyl-2-oxabicyclo[4.3.0]nonan-3-one with complete diastereocontrol in reactions catalyzed by dirhodium(II) tetrakis[methyl 1-(3-pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 49 publications
2
69
1
Order By: Relevance
“…For example, Doyle and co-workers reported chiral rhodium(II) carboxamidate-catalyzed intramolecular CH insertion reactions with enantiomerically pure 2-substituted cyclohexyl diazoacetate 36, which were derivatized from an alcohol (Scheme 17). 24 By using different chiral catalysts (a matched vs. mismatched situation), excellent site-selectivity was achieved with complete diastereocontrol. They further expanded the substrate scope to steroidal diazoacetates 39, in which the fivemembered ring product 40 is predominantly formed over the four-membered ring β-lactone product by using the chiral [Rh 2 (5R-MEPY) 4 ] catalyst.…”
Section: Metal-carbene and -Nitrene Insertionmentioning
confidence: 99%
“…For example, Doyle and co-workers reported chiral rhodium(II) carboxamidate-catalyzed intramolecular CH insertion reactions with enantiomerically pure 2-substituted cyclohexyl diazoacetate 36, which were derivatized from an alcohol (Scheme 17). 24 By using different chiral catalysts (a matched vs. mismatched situation), excellent site-selectivity was achieved with complete diastereocontrol. They further expanded the substrate scope to steroidal diazoacetates 39, in which the fivemembered ring product 40 is predominantly formed over the four-membered ring β-lactone product by using the chiral [Rh 2 (5R-MEPY) 4 ] catalyst.…”
Section: Metal-carbene and -Nitrene Insertionmentioning
confidence: 99%
“…[1][2][3][4] They exhibit a high preference for the formation of five-membered rings and, in the absence of conformational restrictions, 5 reactivity follows the order tertiary> secondary>> primary. 6 There are few examples of insertion reactions favoring ring sizes other than five in these reactions, 1,[7][8][9] even when electronic influences would justify them. 10 Recently, Davies and coworkers have demonstrated that aryldiazoacetates exhibit much higher levels of selectivity in C-H insertion reactions.…”
mentioning
confidence: 99%
“…7 The corresponding b-lactone, if formed at all, is a very minor product. In contrast, diazo decomposition of cyclohexyl phenyldiazoacetate 6 gives the corresponding b-lactone product 7 17 with near exclusivity (Table 2), and the catalyst had virtually no influence on regioselectivity.…”
mentioning
confidence: 99%
“…The reaction is believed to proceed via equatorial C-H bond insertion, with the cis-and trans-isomeric products resulting from equilibration between the two possible cyclohexyl chair conformations of the diazoacetate. Such a preference for equatorial C-H bond insertion over axial insertion has been widely observed in carbenoid reactions of cyclohexyl diazoacetates, 10,116,121,122 with only very few exceptions being noted to date. As previously discussed, the choice of catalytic system can often be a key decision in determining the regiochemical outcome of intramolecular C-H insertion reactions.…”
Section: Methodsmentioning
confidence: 94%